Pelvic Kidney Mimicking Skeletal Metastasis on Bone Scan- Interesting Image (Bangladesh Journal of Nuclear Medicine, 2021)
A 57-year-old female patient underwent left breast-conserving surgery with sentinel lymph node biopsy for Left breast carcinoma (stage IIA). The patient had hypertension and diabetes mellitus. Other findings include multiple hepatic cyst, bilateral renal cysts and uterine myoma. She had no significant renal symptoms and her liver &renal function test were normal.She was sent for Technetium-99m-methylene diphosphonate (99mTc-MDP) bone scan. There was a large area of intense tracer concentration in the region of right sacro-iliac (SI) joint which appeared like an osteoblastic metastasis at first glance. However, absence of uptake in the right renal fossa with the left kidney being normal in position contemplated the probability of right-sidedpelvickidneywhich was confirmed later by a contrast enhanced computerized tomography (CT) scan of abdomen that showed a pelvic right kidney overlying the sacrum.Bangladesh J. Nuclear Med. 22(2): 155-156, Jul 2019